Pengaruh Jumlah Uang Beredar terhadap Pertumbuhan Ekonomi melalui Investasi sebagai Variabel Intervening pada Provinsi Sumatera Utara - Sari, Arsiska; Syahbana, Eza; Alisya, Jeane; Batubara, Radja Marihat; Marbun, Jonatan; Silaban, Putri Sari Margaret Julianty (Innovative: Journal Of Social Science Research, 2025)
This study analyzes the impact of money supply on economic growth with investment as an intervening variable in North Sumatra during the 2010-2023 period. Using path analysis and secondary data from BPS and Bank Indonesia, the results show that money supply significantly affects economic growth (probability 0.0004) and investment (t-statistic 5.701674; probability 0.0001). Investment also significantly influences economic growth (probability 0.0385) and mediates the relationship between money supply and economic growth (Sobel test, 2.1726; probability 0.0298). The coefficient of determination indicates that 94.4% of the variation in economic growth is explained by money supply and investment. These findings support Keynesian and Harrod-Domar theories on the importance of liquidity and investment. The study recommends integrated monetary and investment policies to support sustainable economic growth in North Sumatra.